Криптосемантична система захисту текстової інформації - Одарченко, Р.С.; Самойлик, Є.О.; Сімахін, В.М.; Боровик, В.О.; Тимчишин, Р.М. (Control systems & computers, 2020)
Запропоновано метод побудови абсолютно стійкої криптосистеми захисту текстової інформації. Метод базується на застосуванні механізму укрупнення абетки мови, в результаті якого збільшується відстань єдиності. Система захисту складається з двох частин: семантичного тезаурусу, розробленого для конкретної прикладної області, та засобів реалізації операторів шифрування/розшифрування, що використовують створений тезаурус Purpose. A method of constructing cryptographically strong cryptosystem, which provides a formal opportunity to encrypt unlimited volumes of text messages. Methods. Lexicographic methods of information security. Results. Usage of the lexicographic mechanism for enlarging the alphabet of the textual information’s language allows increasing the unicity distance, which is the main threshold indicator for the cryptosystem to belong to the class of cryptographically strong security systems with theoretically proven ideal information-theoretic stability. Images’ space of a given subject area of an information system application is mapped onto the space of semantic images of this system, taking into account the semantic relationships between them, which are determined by a given restrictive conditions. This is the basis of the thesaurus structure, which allows during encryption to replace the message to be encrypted with other plausible messages that reflect the true meaning of outgoing messages. Цель. Метод построения абсолютно устойчивой криптографической системы, которая обеспечивает формальную возможность шифрования неограниченных объемов текстовых сообщений. Методы. Лексикографические методы защиты информации. Результаты. Применение лексикографического механизма укрупнения алфавита языка для отображения текстовой информации позволяет увеличить так называемое расстояние единственности, которое является основным пороговым показателем принадлежности криптосистемы к классу абсолютно устойчивых систем защиты с теоретически доказанной идеальной теоретико-информационной устойчивостью. Пространство образов заданной предметной области применения информационной системы отображается на пространство смысловых образов этой системы с учетом семантических соотношений между ними, которые определяются заданным пространством ограничительных условий. Это является основой структуры тезауруса, который позволяет во время шифрования заменять сообщение, подлежащие шифрованию, на другие правдоподобные сообщения, отражающие истинный смысл исходящих сообщений.